Formation of the Economic and Legal Basis for the Development of Organic Farming in Ukraine Through the Prism of European Experience and Attracting Foreign Investment - Piddubna, Daria; Shekhovtsova, Viktoriia; Melnychuk, Olha; Pypiak, Mykola (European Journal of Sustainable Development, 2019)
The natural resources as the constituent of the natural environment and their condition are determined, which requires immediate action. The interaction of a person, his activity with the natural environment is characterized. Economic indicators, including price policy, social guarantees, protection and protection of economic activity in comparison with the international and European status are determined. The analysis of components of the environment in Ukraine is given and the legal bases for the settlement and protection of human rights and freedoms are defined. Potentially possible activities for Ukraine are outlined. The vectors of development and support from the state of Ukraine are analyzed. The direction of development of farming, which today is defined as the creation of a legal entity, with the statute, mandatory state registration, with the opening of an account in a financial institution, is determined in the framework of the current regulatory framework. Attention is drawn to the support of family forms of economic activity at the European level. In order to protect natural resources as constituents of the natural environment and components of human life, it is proposed to take measures to support and develop small and medium business entities, as well as directly owners of land plots, including land plots (shares). The prospects for the introduction of organic farming in Ukraine as an element of the state of the environment change are determined. The necessity of taking a number of economic and legal actions that will be directed not only to protect and protect the rights of citizens of Ukraine but also to meet the commitments that Ukraine has assumed through European integration will meet the generally accepted international and European requirements in the field of conducting international relations for different vectors, and also create conditions for attracting foreign investments into Ukraine. Keywords: economic and legal basis, organic farming, European experience, foreign investment, natural resources, environment, landowners, farming, agro-chemicals and pesticides, price policy.